-8(3+7x)+5=39+2x

Simple and best practice solution for -8(3+7x)+5=39+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(3+7x)+5=39+2x equation:


Simplifying
-8(3 + 7x) + 5 = 39 + 2x
(3 * -8 + 7x * -8) + 5 = 39 + 2x
(-24 + -56x) + 5 = 39 + 2x

Reorder the terms:
-24 + 5 + -56x = 39 + 2x

Combine like terms: -24 + 5 = -19
-19 + -56x = 39 + 2x

Solving
-19 + -56x = 39 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-19 + -56x + -2x = 39 + 2x + -2x

Combine like terms: -56x + -2x = -58x
-19 + -58x = 39 + 2x + -2x

Combine like terms: 2x + -2x = 0
-19 + -58x = 39 + 0
-19 + -58x = 39

Add '19' to each side of the equation.
-19 + 19 + -58x = 39 + 19

Combine like terms: -19 + 19 = 0
0 + -58x = 39 + 19
-58x = 39 + 19

Combine like terms: 39 + 19 = 58
-58x = 58

Divide each side by '-58'.
x = -1

Simplifying
x = -1

See similar equations:

| -2v-4=-2v | | 4x+27=x+12 | | 5(2x-2)=3(4-2x) | | -2-5n=-5n^2 | | 3x+9/15=6 | | 8x^2+8xy-20y=0 | | -x+9=1/3(-9x+6)+1 | | -3(3r+3)=5-7r | | 5x-1-4x=x+17 | | 16-7*2= | | N^2+6=5N | | -3n+9+8n=7n-8n-9 | | 12x+2=4x-22 | | n+7/4=7/20 | | 5x=5/8 | | (4y-1)+(2x+5)=180 | | 6n-2=6n-7 | | 6w^2+24w-72=0 | | A^2-3A-3=5 | | 2x-16-x=x-16 | | 5x^2+24=0 | | 3y^2+51y+90=0 | | 3x=24*0.5 | | 3x+9/15=16 | | 8-9x=80 | | -x^2=36 | | -6x-10=-4x-14 | | 2x-21-x=x-21 | | 3xx-1=x+4 | | -9x-8=x-48 | | 37=5-x+3x | | -4/3t=-16 |

Equations solver categories